TECHNICAL IMPLEMENTATION OF SPIRAL TAPING IN REDUCING PAIN IN ATHLETES COMPLAINANTS PARTICIPATING CATARINENSE UNIVERSITY GAMES 2008 (Fiep Bulletin - online, 2011)
Sport when practiced through competitive exposes its individuals the threshold between yield and injury. In many cases the sport generates so singular, that are considered harmful effects to the expected yield. Search by techniques that minimize these grievances can be useful for the application in sports. The spiral taping is a technique of collage of tapes with therapeutic indeed in reducing pain, inflammatory processes, muscle relaxation and energy balance of the organism (TANAKA, 2007). The goal of this study was to assess subjectively perceived pain resulting from injury of athlete tissue before and after applying the technique spiral taping before the discomfort. The sample was comprised of 34 (28-82.4% male and female 06-17.6%) with an average age of athletes 21.5 ± 3.0 years, participants of the University of Santa Catarina Games 2008, which reported pain mio-articulate and agreed to participate in the study as the resolution 196/96. Was conducted an assessment of pain pre and post implementation with muscle testing through employment of perceived pain scale CR-10 proposed by Borg (2000). As results unable to determine that: in the application, the average score that stayed in 4.6 ± 2.12) and postgraduate application the average cut for 1.7 ± 1.68 CR-10 scale. Succeeded the average decline of sensation of pain will 67.4% in individuals. Conclusions: the technique spiral taping proved to be an effective method in intervention and management of reduction and removal of pain in athletes attacked by injuries in sport, being that the pain was suppressed in more than half of the athlete's complainants (p < 0.05). Thus keeping a conduct applicable and low cost in order to improve the health status of complainants. Noted that this is a stopgap measure requiring specialized interference.
Keywords: Pain; Spiral Taping; College Athletes